Kajian Teknik dan Efisiensi Pemasaran Karang Hias (coral) Jenis Euphyllia Glabrescens pada PT. Agung Aquatic Marine Badung, Denpasar Bali - Aulia Riska; Nur Alam Kasim; Megawati Megawati (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
The purpose of this study was to determine the marketing techniques of ornamental coral (coral) type Euphyllia Glabrescens at PT. Agung Aquatic Marine. and to determine the efficiency of direct marketing of ornamental coral (Coral) type Euphyllia Glabrescens at PT. Agung Aquatic Marine. The type of research used is qualitative and quantitative methods with data collection techniques of observation, interviews, and documentation, the analysis technique used in this study uses qualitative descriptive analysis. The results of the analysis of sales data of ornamental coral (Coral) type Euphyllia Glabrencens at PT. Agung Aquatic Marine uses three techniques in marketing ornamental coral (Coral), namely face to face, stock list, and via photos. Between the two marketing channels there are differences in efficient marketing results, but between the two marketing channels, the most efficient in marketing ornamental coral is marketing channel I with an efficiency level of 1.0%, while marketing channel II has an efficiency level of 0.49%. This is because in marketing channel I, the costs incurred are slightly lower than those in marketing channel II, which has a larger cost component because the shipping distance of ornamental coral is quite far.